Follow the Leader? The unequal distribution of attention in social media - Schlögl, Stephan (Momentum Quarterly, 2015)
This article deals with the mechanisms of unequal distribution of attention in social media based on a case study of Tweets about the UN Conference on Sustainable Development in Rio in 2012 (RIO+20). Inequality is discussed in relation to a normative concept of Public Sphere mainly inspired by Jürgen Habermas. The author uses Georg Franck’s “economy of attention” as an analytical framework in order to understand how attention is managed in different types of computer-mediated communication platforms. The case study then shows that attention is heavily unequally distributed among the participants and it is further investigated how social and technical mechanisms lead to this. Finally the author argues that the inequality of twitter users in terms of attention is not a mere characteristic of the case, but one of the basic principles of social media like twitter.